Constructive strategy and analysis on engineered application of 4G small base station - Weiping LI (Dianxin kexue)
The strategy and suggestions about the scene of 4G small base station based on network architecture of TD-LTE were described.Some problems at the engineering applications were combed,items were analyzed and the solving methods were introduced.